Director of the Faculty Therapeutic Clinic Nikolay Fedorovich Golubov: Scientific Activity, Last Years of Life and Finding of the Lost Grave (by the 165th Anniversary from Birthday) - Y. A. Lutokhina; O. V. Blagova; A. I. Zaitseva; A. V. Nedostup (Рациональная фармакотерапия в кардиологии, 2021)
September, 2021 marks the 175th anniversary of the opening of the Faculty Therapeutic Clinic (FTC) of the Imperial Moscow University, which is a successor of the First (1805) and Second (1820) Clinical Institutes with their therapeutic beds and chairs, and thus is the oldest therapeutic clinic in Russia. From 1930 the Clinic became part of the newly formed I.M. Sechenov First Moscow Medical Institute (now Sechenov University) and retains continuity to the present day. This publication is one of three research articles prepared by the staff of the Clinic for the anniversary and devoted to little-known pages of biography and scientific activities of the three heads of the FTC at the crucial stages of its history – A.I. Over, G.A. Zakharyin and the last prerevolutionary director – N.F. Golubov.